Utilization of concentrate by beef calves proceeding from integral milk and replacer feedings - Reis, Silvia J.; Andrade, Pedro de; Andrade, Antonio Tadeu de; Oliveira, Mauro Dal S. de; Sampaio, Alexandre A. M. (Pesquisa Agropecuaria Brasileira, 2014)
This work was conducted in order to study the effect of use of the whole milk, commercial milk replacer and one milk replacer made with soybean meal, in the liquid diet fase, with two concentrate levels (100% and 75% of National Research Council 1966 requirements), on the performance of calves. Twenty four Holstein calves were utilized in four randomized blocks, and factorial design 3 x 2. It was concluded that the food nature utilized up to the 56th, day did not affect gain of weight, hay intake or feed conversion of calves in late rearing fase from 2th to 6th months of age, but weight gain was influenced by concentrate levels (P<0,05).